Case report: A patient with HHV-6 and HHV-7 combined with Whipple’s trophoblast infection and streptococcal pneumonia - Chen, Heng; Zhao, Bo; Yang, Jing; Li, Pi-bao (Frontiers in Medicine, 2024)
Adult respiratory distress syndrome due to viral pneumonia occurs predominantly in immunodeficient populations; adult respiratory distress syndrome secondary to human herpesvirus HHV-6 and HHV-7 pneumonia is extremely rare. Whipple's disease, caused by Tropheryma whipplei, a Gram-positive bacillus and obligate intracellular pathogen, is clinically challenging to diagnose. Whipple's disease is a chronic multisystem infectious disease caused by T. whipplei, most often affecting the gastrointestinal tract and joints, seldom the lungs. Both pathogens are opportunistic. We report a case of mixed infectious pneumonia in a patient with type 2 diabetes mellitus. The patient presented with dyspnea and intermittent fever. Imaging revealed multiple large patchy consolidations in the left lung. Routine anti-infective therapy was ineffective. Metagenomic next generation sequencing of bronchoalveolar lavage fluid indicated HHV-6 and HHV-7 pneumonia concurrent with T. whipplei and Streptococcus coinfections. Meropenem was administered to improve treatment. This case represents a rare mixed lung infection by multiple uncommon pathogens, and is of particular clinical significance.